Randomized, Parallel Group, Open-Label Bioequivalence Trial of Intramuscular Pegaspargase in Patients With Relapsed Acute Lymphoblastic Leukemia - Manjunath Nookala Krishnamurthy; Gaurav Narula; Khushboo Gandhi; Ankita Awase; Ruta Pandit; Sunil Raut; Ritu Singh; Vikram Gota; Shripad Dinanath Banavali (JCO Global Oncology, 2020)
PURPOSE Pegylated asparaginase is comparatively safer than native asparaginase in the management of acute lymphoblastic leukemia (ALL). However, the high price and nonavailability in low- and middle-income countries limits its use. In 2014, the first generic of pegaspargase (Hamsyl) was approved in India for use as a second-line treatment option for ALL. The aim of this study was to assess whether the generic pegaspargase (the test product) was bioequivalent with the reference product (Oncaspar). PATIENTS AND METHODS This study was an open-label, parallel-group, comparative pharmacokinetic study in pediatric patients with relapsed ALL receiving their first dose (1,000 IU/m2) of pegaspargase administered intramuscularly. Patients were randomly assigned 1-to-1 to either the test or the reference product. The 2 formulations were considered equivalent if the 90% CIs for area under the plasma asparaginase activity–time curve (AUC0-t) geometric mean test-to-reference ratio was within 75% to 133%. RESULTS Twenty-nine patients (6-18 years of age) were enrolled in this study, of whom 24 completed the study criteria and were considered for safety analysis (5 patients were ineligible for the assessment). Three patients were excluded from analysis, because of presence of anti-asparaginase antibodies, leaving 21 patients who were considered for bioequivalence pharmacokinetics data. The point estimate of AUC0-t for the test-to-reference ratio was 95.05 (90% CI, 75.07% to 120.33%). Maximum plasma concentration, trough concentrations (day 14), half-life, volume of distribution, drug clearance, and changes in the asparagine and glutamine levels were not significantly different between products. Adverse events were comparable in both groups. CONCLUSION Generic and reference pegaspargase had equivalent pharmacokinetics with comparable safety. This could be a safe and cost-effective alternative for patients with ALL, especially in low- and middle-income countries.